Jane Hornby: Fresh and Easy: What to Cook and How to Cook it - Storey, Jennifer (Petits Propos Culinaires, 2013)
Jane Hornby: Fresh and Easy: What to Cook and How to Cook it, Phaidon, 2012, 351 pp., hardback, £29.95.